Cardiopulmonary function in adolescent patients with pectus excavatum or carinatum. Issue 1 (29th July 2021) - Ramadan, Salim; Wilde, Jim; Tabard-Fougère, Anne; Toso, Seema; Beghetti, Maurice; Vallée, Jean-Paul; Corbelli, Regula; Barazzone-Argiroffo, Constance; Lascombes, Pierre; Ruchonnet-Métrailler, Isabelle
Abstract : Background: Pectus excavatum (PE) and pectus carinatum (PC) have generally been considered an aesthetic issue, although there is growing evidence of associated cardiopulmonary function (CPF) impairment, especially in PE patients. The study goal was to determine any correlation between pectus malformations and cardiopulmonary symptoms and function based on systematic assessment of CPF and thoracic measurements, such as Haller Index (HI) and sternal torsion angle (STA). Methods: Data from 76 adolescent patients with PE (n=30) or PC (n=46) were retrospectively collected referred between January 2015 and April 2018. CPF measurements and thoracic imaging were performed in all patients. HI and STA correction indexes were measured in all patients. Findings: Medical records from 76 patients (PE n=30; PC n=46) were analysed. Patients were predominantly male (>93.3%), and aged between 13 and 14½ old. PE was associated with airway obstruction, with a forced expiratory volume in 1 s value under the lower limit of normal in 13% of cases (p<0.001). Restrictive syndrome was observed in 23% of cases (p<0.001), with a Z score for total lung capacity under the lower limit of normal. In PC, pulmonary function was not affected. All patients showed slightly decreased values of left and right ejection fraction and cardiac index at rest, although values were within normal range. There were no significant correlations between pulmonary and cardiac functions or between low CPF and thoracic measurements. Interpretation: Our results confirm the modest impact of pectus malformations on CPF at rest, without correlation with anamnestic dyspnoea on exertion, nor with chest pain or anatomical measurements. Validation of new correction indexes could be helping characterise these malformations and choose optimal therapeutic management.